Cooperation Agreement Between Lisawati Tax Consultants And The Anggoro Kasih Pamekasan Foundation In Connection With Book Iii of The Data Code - Lisawati; Mohammad Roesli; Bastianto Nugroho (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The purpose of knowing the procedure for implementing a work agreement between the Lisawati Tax Consultant and the Anggoro Kasih Pamekasan Foundation in relation to Book III of the Civil Code.This research uses the method The type of research in this study is normative juridical law research, namely research based on literature studies which includes primary legal materials and secondary legal materials. Hasil Legal consequences if one party does not carry out its obligations can occur due to 2 (two) things, namely due to default and overmacht. default carried out by the Lisawati Tax Consultant if since the signing of the deed of agreement the Lisawati Tax Consultant has not issued an SPK, then for this negligence the Lisawati Tax Consultant may be subject to sanctions in the form of reimbursement for losses for planning work implementation, while the default is carried out by the Anggoro Kasih Pamekasan Foundation if after the issuance of the SPK, the Anggoro Kasih Pamekasan Foundation is late / does not carry out achievements, then for the delay the Anggoro Kasih Pamekasan Foundation is only obliged to pay a number of items that have been made by the Lisawati Tax Consultant only and as a penalty the agreement is considered null and void and cannot be continued for any reason, the legal consequences of overmacht if it is only temporary, the debtor can request a delay in fulfilling the achievement and if it is absolute/permanent, then the agreement is automatically canceled.